Is the Conventional View of Discount Window Borrowing Consistent with the Behavior of Weekly Reporting Banks? - Cosimano, Thomas F.; Sheehan, Richard G. (The Review of Economics and Statistics, 1994)
Discount window borrowing by weekly reporting banks disaggregated by Federal Reserve district is used to estimate Marvin Goodfriend's (1983) model of borrowed reserves. Little evidence is found to support the argument that a bank's borrowing decision is determined by the spread between the funds rate and the discount rate and by prior bank borrowing. A weekly reporting bank has only a 2.7 percent chance of visiting the discount window during any given maintenance period. This result is consistent with the presence of considerable harassment costs imposed by the discount window officer. Copyright 1994 by MIT Press.